VEGF in age-related macular degeneration. Part II. VEGF inhibitors use in age-related macular degeneration treatment - Wylęgała, Edward; Teper, Sławomir (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
Wet AMD remains a therapeutic challenge. VEGF inhibitors are new promising group of medical agents undergoing advanced clinical trials. Oncology is the main specialty using anti-VEGF therapy. Two agents were designed from the beginning as ophthalmologic medicines. These are pegaptanib and ranibizumab. In the paper there is mechanism, efficacy and safety data presented, especially coming from multi-center randomized clinical trials. Monoclonal VEGF-antibodies (ranibizumab and bevacizumab) seem to be most effective in wet AMD treatment. Because of important physiological VEGF role long-term observation is needed to confirm safety of VEGF inhibition.